2010
DOI: 10.1086/650203
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flagellin Stimulates Toll‐Like Receptor 5–Dependent Defense against Vancomycin‐ResistantEnterococcusInfection

Abstract: Treatment of vancomycin-resistant Enterococcus (VRE) infections is limited by the paucity of effective antibiotics. Administration of broad-spectrum antibiotics promotes VRE colonization by down-regulating homeostatic innate immune defenses. Intestinal epithelial cells and Paneth cells express antimicrobial factors upon direct or indirect stimulation of the Toll-like receptor (TLR)-MyD88-mediated pathway by microbe-derived molecules. Here, we demonstrate that the TLR5 agonist flagellin restores antibiotic-impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
190
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(213 citation statements)
references
References 47 publications
14
190
2
3
Order By: Relevance
“…The effect of TLR signaling on IL-17 and IL-22 was previously suggested because their synthesis was enhanced after administration of TLR2 and TLR4 agonists (12,29). Very recently, TLR5 signaling was also associated to such response (40). In this study, we analyzed the immune response to the TLR5 activator The Journal of Immunologyflagellin, with a focus on mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of TLR signaling on IL-17 and IL-22 was previously suggested because their synthesis was enhanced after administration of TLR2 and TLR4 agonists (12,29). Very recently, TLR5 signaling was also associated to such response (40). In this study, we analyzed the immune response to the TLR5 activator The Journal of Immunologyflagellin, with a focus on mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Flagellin-mediated protection of rodents and nonhuman primates against lethal irradiation was associated with CSF3-mediated granulopoiesis and the antiapoptotic effect of superoxide dismutase 2 (47). Flagellin treatment has been linked to resistance against inflammatory colitis and gut infections (40,48). The TLR5-induced circulating and local production of IL-17/IL-22 may be the main driving force behind these protective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, differentiation of Th17 cells in the lamina propria of the small intestine is correlated with the presence of bacteria from the Cytophaga-FlavobacteriumBacteroides group [92]. Additionally, the stimulation of TLR5, mediated by flagellin, triggers the expression of IL-6, inducing Th17 cell programming [93]. Moreover, polysaccharide A from B. fragilis can protect from inflammatory diseases such as colitis by suppressing pro-inflammatory IL-17-producing CD4 + T cells and inducing IL-10-producing CD4 + T cells [94].…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…46 Administration of oral lipopolysaccharide or systemic flagellin to antibiotic-treated mice re-induces RegIIIg expression and reduces intestinal colonization with VRE. 46,47 Recent studies using the mouse model demonstrated that stimulation of TLR5 with flagellin increases resistance to C. difficile infection. 48 Although it is unclear whether TLR5-mediated protection against C. difficile infection is mediated by RegIIIg, recent studies have demonstrated that MyD88-deficient mice are highly susceptible to C. difficile infection and that MyD88-signaling is required for neutrophil recruitment to the gut, an essential step for survival of infection.…”
mentioning
confidence: 99%